Dendritic cells and vaccine design for sexually-transmitted diseases - Duluc, Dorothee (2012)
Dendritic cells (DCs) are major antigen presenting cells (APCs) that can initiate and control host immune responses toward either immunity or tolerance. These features of DCs, as immune orchestrators, are well characterized by their tissue localizations as well as by their subset-dependent functional specialties and plasticity. Thus, the level of protective immunity to invading microbial pathogens can be dependent on the subsets of DCs taking up microbial antigens and their functional plasticity in response to microbial products, host cellular components and the cytokine milieu in the microenvironment. Vaccines are the most efficient and cost-effective preventive medicine against infectious diseases. However, major challenges still remain for the diseases caused by sexually-transmitted pathogens, including HIV, HPV, HSV and Chlamydia. We surmise that the establishment of protective immunity in the female genital mucosa, the major entry and transfer site of these pathogens, will bring significant benefit for the protection against sexually-transmitted diseases. Recent progresses made in DC biology suggest that vaccines designed to target proper DC subsets may permit us to establish protective immunity in the female genital mucosa against sexually-transmitted pathogens.